Q. 94.0( 6 Votes )

Prove: <span lang

Answer :

FORMULA: -


(i)


Proof:



cosx + cos (120 – x) + cos (120 + x) = cosx + 2cos120 cos( – x)


cosx + cos (120 – x) + cos (120 + x) = cosx + 2cos(180 – 60) cosx


cosx + cos (120 – x) + cos (120 + x) = cosx + 2 ( – cos 60) cosx



cosx + cos (120 – x) + cos (120 + x) = cosx – cosx


cosx + cos (120 – x) + cos (120 + x) = 0


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

If A + B + C = π,RS Aggarwal - Mathematics

If A + B + C = π,RS Aggarwal - Mathematics